Mental Health from the Perspective of Positive Psychology and the Concept of Patience and Gratitude in Islam - Rudi Herianto (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Mental health is increasingly understood as a multidimensional condition involving psychological functioning, meaningful relationships, positive emotions, and the ability to respond constructively to life challenges. Positive psychology provides an important framework for understanding these dimensions through human strengths, flourishing, meaning, and well-being. However, psychological perspectives alone may not fully capture the spiritual dimensions of mental health within Muslim communities. This study examines mental health from a positive psychology perspective and explores the relevance of sabr (patience) and shukr (gratitude) in Islam as complementary psychological and spiritual resources. The study employed a qualitative library research design by examining relevant psychological literature, Islamic sources, peer-reviewed journal articles, academic books, and classical works concerning positive psychology, mental health, sabr, and shukr. The literature was analyzed through qualitative content analysis involving data reduction, thematic coding, conceptual comparison, and integrative interpretation. The findings indicate that sabr has conceptual relevance to self-regulation, coping, persistence, and resilience, while shukr is associated with positive emotional experiences, life satisfaction, meaning, and social connectedness. Nevertheless, neither concept should be treated as a direct equivalent of a Western psychological construct because both retain distinctive ethical and spiritual meanings within Islam. The integration of these perspectives suggests that sabr and shukr can complement positive psychology by connecting psychological functioning with spiritual orientation and meaning-making. This integrated perspective offers a culturally responsive foundation for understanding and promoting holistic mental health in Muslim contexts.